Blockchain como herramienta para el mejoramiento de los procesos de comercio exterior en Colombia (2020)
At the present time, Colombia has a low logistics point index in comparison to other countries of the region and members of the Organization for Economic Co-operation and Development (OECD), this is a result of long, expensive, insecure, inefficient and vulnerable processes. An innovative tool was found to be successful alleviating similar problems: blockchain, thus though document tracking, the present investigation was made to determine how to implement blockchain in Colombia to improve the logistics point index in matter of supply chain, customs management and international payments. A relevant result was the successful function that the blockchain has achieved by improving the supply chains and document processes of many companies around the world, as well as facilitating payments internationally, bearing in mind that some of those companies are Colombian, we conclude that Colombia is ready to take steps towards the modernization and digitization of processes to improve its levels of competitiveness and that blockchain is the optimal technology to achieve these objectives